Risk factors associated with the occurrence of precancerous cervical lesions at health centres of Karanganyar regency - Purwaningsih, Heni; Prajatmo, Heru; Widyawati, . (International Journal Of Community Medicine And Public Health, 2017)
Background: Precancerous cervical lesions is sign of cervical cancer. The development of precancerous cervical lesions is difficult to detect, so it is recommended every woman conduct examination by using visual inspection with acetic acid (VIA) because it is inexpensive and effective. The number of cervical cancer screening Health Department of Karanganyar Regency in 2014 was 3285 people and 345 people positive for precancerous cervical lesions. The figure is very less considering the achievement of the target number is 120244 people with target every years 19239 people. Methods: Analytical research with case control design. The number of sample was 40 women positive IVA and the control sample were 40 women with negative IVA. Samples were taken with consecutive sampling technique in June-August 2015 at Health Centres of Karanganyar Regency. Data analysis used chi-square and logistic regression. Results: Results of chi-square analysis found there is significant relationship between age, age when they have first intercourse, number of partners, social and economic parity (p<0.05). Results of logistic regression test found significant risk factor is number of partners OR=5,026 (CI 95% 1,265 - 19,973). Conclusions: The most dominant risk factors on the incidence of precancerous lesions of the cervix are the number of couples. Suggested to the health center staff to identify, advice and motivate women the risk of precancerous lesions of the cervix examination IVA.